KAJIAN HUBUNGAN PANJANG BERAT DAN FAKTOR KONDISI IKAN NILA (Oreochomis niloticus) PEMBESARAN KOLAM TANAH DI DESA A. WIDODO, TUGUMULYO, MUSI RAWAS, SUMATERA SELATAN - La Ode Wahidin; Sri Murtini; Dwi Wulandari Retno Wulandari; Rohman Isnaini; Indah Febriana; Setiono Setiono (LPPM Universitas Bina Insan, 2021)
Nile Tilapias (Oreochomis niloticus) have been cultured and being a fresh water fishery commodity for a long time in Musi Rawas Regency. The optimal growth of this fish plays a significant role for fishermen due to relating on costs and harvest periods. This research was aimed at analysing the length-weight relationship as well as condition factor of the tilapia reared in a soil-pond. It was conducted on December 2020 at the Fishery and Environmental Engineering Laboratory of Bina Insan University, Lubuklinggau. Samples of the fish acquired from commercial fish-soil-pond culture at A Widodo Village, Tugumulyo Sub-district, Musi Rawas Regency. Those fish consisted of five weight-class categories namely each kilogram containing 8 fish, 7 fish, 6 fish, 5 fish, and 3 fish, respectively. Data of the fish were analysed for length, weight, sexual characteristics, sex ratio, and gonadal mature level as well as the condition factor. Data were tabulated and figured in Microsoft Excel. Determining the fish growth pattern used SPSS Software. Results of this research indicate averages of length and weight for all fish (29 individuals) are 20.72 cm and 162.72 grams, respectively. Dominantly sex of all fish is male, and a ratio of female and male is 0.380. The identified female fish are in gonadal mature level 2-3. The male fish, in common, are in a weight of 7-8 fish in a kilogram. The growth pattern of fish is negative allometric (coefficient regression of 1.3556) denoting the length grows quicker than weight. The condition factor is about 1.828 represents the cultured fish were categorizing into fatty fish.